Mergers of Binary Neutron Star Systems: A Multimessenger Revolution - Pian, Elena (Frontiers in Astronomy and Space Sciences, 2021)
On 17 August 2017, less than two years after the direct detection of gravitational radiation from the merger of two ~30 Msun black holes, a binary neutron star merger was identified as the source of a gravitational wave signal of ~100 s duration that occurred at less than 50 Mpc from Earth. A short GRB was independently identified in the same sky area by the Fermi and INTEGRAL satellites for high energy astrophysics, which turned out to be associated with the gravitational event. Prompt follow-up observations at all wavelengths led first to the detection of an optical and infrared source located in the spheroidal galaxy NGC4993 and, with a delay of ~10 days, to the detection of radio and X-ray signals. This paper revisits these observations and focusses on the early optical/infrared source, which was thermal in nature and powered by the radioactive decay of the unstable isotopes of elements synthesized via rapid neutron capture during the merger and in the phases immediately following it. The far-reaching consequences of this event for cosmic nucleosynthesis and for the history of heavy elements formation in the Universe are also illustrated.